On the use of the design of experiments theory in individual dataanalysis - Złotoś, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The methods of the design of experiments are one of tools which are used in statistical quality control. The application of the design of experiments in the projection or modification of the manufacturing process leads to the improvement of the technological parameters and to reducing the overall costs of the process. Among the designs of experiments it is possible to indicate the classic and factorial designs of experiments. Nowadays the theory of the design of experiments applies in natural science and in the analysis of the spatial data. Microeconometrics is the part of econometrics which was developed in the 1950s. Microeconometric research deals with the analysis of individual data called microdata, which are increasingly used in research in the fields of economics, management and finance. The aim of this paper is to present the possibility of using the theory of experimental design in the analysis of the individual data. The proposed method will be presented for a selected set of individual data.
Mathematical Economics; 2017; Nr 13 (20); s. 95-106
Keywords: design of experiments; individual data; response surf